Farmer perceptions of agricultural risks: Which risk attributes matter most for men and women - Osiemo, Jamleck; Ruben, Ruerd; Girvetz, Evan Hartunian (MDPI, 2021)
Analysis of farmer risk perceptions is usually limited to production risks, with risk perception as a function of likelihood and severity. Such an approach is limited in the context of the many risks and other important risk attributes. Our analysis of the risk perceptions of farmers extends beyond production risks, severity of the risks, and their likelihoods. We first characterize agricultural risks and identify their main sources and consequences. We then analyze risk perceptions as a hierarchical construct using partial least squares path modelling. We determine the most important risks and risk attributes in the perceptions of farmers, and test for differences in the perceptions between men and women. Results show that severity and ability to prevent a risk are most important in forming risk perceptions. Second, probabilities (ability to prevent) tend to matter more to men (women) for some risks; lastly, low crop yields and fluctuating input prices have greater total effects on the overall risk perception. Our results provide an impetus for risk analysis in agriculture to consider risk attributes that cause affective reactions such as severity and perceived ability to prevent the risks, the need for input price stabilization, and redress of the rampart yield gaps in small-scale agriculture.